2011
DOI: 10.1002/hbm.21182
|View full text |Cite
|
Sign up to set email alerts
|

Event‐related potential activity in the basal ganglia differentiates rewards from nonrewards: Temporospatial principal components analysis and source localization of the feedback negativity

Abstract: Event-related potential studies of reward processing have consistently identified the feedback negativity (FN), an early neural response that differentiates feedback indicating unfavorable versus favorable outcomes. Several important questions remain, however, about the nature of this response. In this study, the FN was recorded in response to monetary gains and losses during a laboratory gambling task, and temporospatial principal components analysis was used to separate the FN from overlapping responses. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

46
343
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 388 publications
(393 citation statements)
references
References 54 publications
(84 reference statements)
46
343
2
2
Order By: Relevance
“…Conversely, we also demonstrated that win outcomes elicit a positive deflection at the same latency, corroborating the findings from other studies (Foti et al, 2011;Holroyd et al, 2003;Holroyd et al, 2008). The results of the current study serve to elucidate how feedback of differing incentive value are processed in the brain, as well as to consolidate and explain the disparate findings of the extant literature -something that is of major significance, as it affords the examination of the effects of both reward and punishment via independent neural correlates that are likely to be generated within the same cortical structure/s and/or system/s.…”
Section: Frn/frpsupporting
confidence: 93%
See 2 more Smart Citations
“…Conversely, we also demonstrated that win outcomes elicit a positive deflection at the same latency, corroborating the findings from other studies (Foti et al, 2011;Holroyd et al, 2003;Holroyd et al, 2008). The results of the current study serve to elucidate how feedback of differing incentive value are processed in the brain, as well as to consolidate and explain the disparate findings of the extant literature -something that is of major significance, as it affords the examination of the effects of both reward and punishment via independent neural correlates that are likely to be generated within the same cortical structure/s and/or system/s.…”
Section: Frn/frpsupporting
confidence: 93%
“…Despite the probability of reward being controlled for in the analysis of the current study, the positive response to win outcomes observed may be exaggerated due to participants perceiving rewards to occur less frequently during the course of the experiment; however, a large positive deflection (i.e., the FRP) to reward outcomes, similar to that found in the current experiment, was also found in a recent study that used a temporospatial PCA to examine equiprobable win and loss outcomes in a simple two-choice gambling task (Foti et al, 2011). That study also found a much smaller FRN to loss outcomes, the reasons for which are unclear; such a result would not be predicted by stimulus frequency effects (losses occurred comparatively more frequently in the current study).…”
Section: Frn/frpsupporting
confidence: 78%
See 1 more Smart Citation
“…However, the theoretical claim of Holroyd and Coles that the FRN constitutes an RPE encoder does require observation of its response to RPE size, by the terms of the axiomatic model. Thus Foti et al's (2011) PCA study successfully isolated the FRN as typically defined but nevertheless cannot be said to have successfully isolated an RPE encoding component. The distinction is far from academic because in our meta-6 analysis we showed that the interval of the feedback-locked ERP that shows an RPE size x valence interaction is considerably smaller than the interval showing a main effect of valence (Sambrook & Goslin 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Given surprisingly high variance explained by this factor (>50%), it is likely that this would have allowed the separation of further frontocentral components. Foti, Weinberg, Dien, and Hajcak (2011) did conduct a temporospatial PCA designed specifically to resolve the question of the relative sensitivity of the FRN to +RPEs and -RPEs. These authors found a factor whose temporospatial profile resembled the FRN, and which responded only to +RPEs.…”
Section: Introductionmentioning
confidence: 99%